31. ACNE STATUS AND ASSOCIATED FACTORS AMONG UNIVERSITY STUDENTS: A CROSS-SECTIONAL STUDY (Tạp chí Y học Cộng đồng, 2024)
Aims: This study aims to assess the prevalence of acne and identify factors associated with its occurrence among students at Đại Nam University.Methods: A cross-sectional study was conducted involving 508 students. Participants were surveyed on demographics, lifestyle habits, and family history of acne. Data were analyzed to determine the association between these factors and the prevalence of acne.Results: The prevalence of acne among the participants was 49.8%, with a slightly higher prevalence in females (50.8%) compared to males (48.0%). Family history of acne was significantly associated with the likelihood of developing acne, with students having family members with acne being 48% more likely to have acne (AOR: 0.48; 95% CI: 0.33-0.71; p
Keywords: Acne status; Related factors; University students; DNU